Using principal component analysis and process behavior charting to answer "Is Secretariat the fastest U.S. racing thoroughbred to date?". Issue 1 (14th January 2021) - Scariano, Stephen M.; Parker, Jillian E.
Abstract: Statistical evidence is presented to answer the title question using graphical tools from process behavior charting as well as ranking methods based on principal component analysis. These tools provide strong data evidence to answer the question convincingly.